SCIENTIFIC JUSTIFICATION FOR VACCINATION OF CHILDREN WITH HEALTH DISTURBANCES - A.A. Baranov; L.S. Namazova-Baranova; V.K. Tatochenko (Педиатрическая фармакология)
(Pediatric Pharmacology. – 2010; 7(2):6-24)